NILAI-NILAI PENDIDIKAN ISLAM DALAM KISAH NABI KHIDIR DAN NABI MUSA (Telaah Q.S Al-Kahfi: 60-82) - Jamilatun Nimah; Muhammad Hanif; Ika Anggraheni (VICRATINA, 2019)
The value of Islamic religious education is required to be the direction of truth because of the moral crisis that occurred in the end of this age. Story is one form of learning to all human beings that is very relevant to the contextualization of the present era, where humans can continue to learn from past experiences that can then be taken good as well as improve or look for positive formulations of what has become a shortage of the past. Likewise with the story of the Prophet Khidr and the Prophet Moses in the letter Al-Kahf verses 60-82. The value of Islamic education contained therein is the value of patience, the value of tawadhu ', meek value, the ethical value of educators to students that is not teaching knowledge that is not mastered by students, resignation value, ethical values of students to educators ie not asking when not welcome ask, must have prejudiced values and values of faith in God's decree. Keywords: Islamic education values, acts